Cultivating the critical imagination: post-disciplinary pedagogy in a computational design laboratory. Issue 4 (2nd October 2019) - Cardoso Llach, Daniel; Ozkar, Mine
ABSTRACT: This article documents and reflects upon a pedagogical project aimed at fostering critical engagements with technology in the context of a graduate research and learning laboratory at the nexus of computer science, design, engineering, and architecture. With the notions of critical technical practice and reflective practice as touchstones, the project links a specific tradition of twentieth century design pedagogy to critical sensibilities drawn from the field of science and technology studies (STS) in a space we call the 'research studio.' The methods and examples presented illustrate how this hybrid pedagogical model can cultivate the critical imagination of learners – their ability to place critical and sociohistorical reflection at the centre of creative technology design – and show that the fields of design and STS offer distinct but mutually enriching traditions of learning and research. The article offers insight to educators and researchers across STEM and humanities fields interested in engaging with technologies not merely as subjects but also as vehicles of scholarly and creative inquiry.